Socialization and education on utilization of UAV (Unmanned Aerial Vehicles) and Village Community Economic Empowerment Through Silvofishery in Kedai Damar Village, Serdang Bedagai, North Sumatra - Arinah, Hafizah; Anggraini, Novita; Purba, Mhd Adanan; Afifah, Nur; Abdillah, Manda Rizky; Ambarita, Winda Lestari; Akbar, Muhammad Syawal; Dimas, Muhammad; Putri, Intan Novita Dwi (Talenta Publisher, 2022)
The service team carried out was entitled